2017
DOI: 10.5624/isd.2017.47.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam computed tomography versus digital periapical radiography in the detection of artificially created periapical lesions: A pilot study of the diagnostic accuracy of endodontists using both techniques

Abstract: PurposeThe aim of this study was to compare the diagnostic accuracy of previously trained endodontists in the detection of artificially created periapical lesions using cone-beam computed tomography (CBCT) and digital periapical radiography (DPR).Materials and MethodsAn ex vivo model using dry skulls was used, in which simulated apical lesions were created and then progressively enlarged using #1/2, #2, #4, and #6 round burs. A total of 11 teeth were included in the study, and 110 images were obtained with CBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
1
11
0
3
Order By: Relevance
“…Campello et al (2017) found that the accuracy of CBCT was much higher than the digital radiography in detecting artificially created periapical lesions. The correct diagnosis recorded using CBCT was 73.6% and by radiograph 56.9% of the cases, the greatest differences being observed in maxillary (71.4% and 28.6%) and multi-rooted teeth (83.3% and 33.3%) respectively [12].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Campello et al (2017) found that the accuracy of CBCT was much higher than the digital radiography in detecting artificially created periapical lesions. The correct diagnosis recorded using CBCT was 73.6% and by radiograph 56.9% of the cases, the greatest differences being observed in maxillary (71.4% and 28.6%) and multi-rooted teeth (83.3% and 33.3%) respectively [12].…”
Section: Discussionmentioning
confidence: 96%
“…In teeth with irreversible pulpitis, the radiography identified the presence of apical pathology in 3% and the CBCT in 14% of the cases [9]. Nevertheless, according to the American Association of Endodontists the CBCT must be considered an adjunct to 2-dimensional imaging techniques reserved only for special cases [12]. Campello et al (2017) found that the accuracy of CBCT was much higher than the digital radiography in detecting artificially created periapical lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La revisión de la literatura coincide en que las radiografías convencionales carecen de sensibilidad para determinar patologías apicales, por el alto ruido que provoca la presencia de estructuras anatómicas, lo cual demuestra que, entre las imágenes 2D, las más certeras son aquellas de tipo digital. En la revisión actual, el 90% de la literatura ofrece datos favorables para el uso de TCHC de campo pequeño; sin embargo, las lesiones apicales de gran tamaño (entre 1.4 mm-1.8mm de diámetro) no presentan diferencias significativas respecto de la técnica imagenológica empleada para su visualización ( [31][32][33][34][35][36] ).…”
Section: Técnicas Radiológicas Usadas Actualmente En El Diagnóstico Yunclassified
“…Moreover, the relative complexity of the region is increased by the presence of superimposing structures that result in "anatomical noise". All of these factors contribute to the difficulty in recognition of bone resorption on radiographic images, which impedes 2 of 14 the accuracy of diagnosis using digital intraoral radiography (DIR) images and may result in periapical lesions going undetected or detection is inadequate [5][6][7].…”
Section: Introductionmentioning
confidence: 99%